Martin Agronsky papers - Agronsky, Martin
Correspondence, radio, television, and film scripts, writings, speeches, research material, notes, clippings, printed material, photographs, and other papers concerning Agronsky's career as a radio and television journalist. Pertains to his work as a foreign correspondent in Europe, Australia, and Asia during World War II and continuing through the Cold War years, his coverage of the Adolf Eichmann trial in Israel, and other political and economic subjects.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Radio and television journalist. Born 1915; died 1999.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Eichmann, Adolf, -- 1906-1962 -- Trials, litigation, etc; Cold War; Economics; Foreign correspondents -- Asia; Foreign correspondents -- Australia; Foreign correspondents -- Europe; Politics, Practical; Trials -- Israel; World War, 1939-1945 -- Journalists; Journalists